Ecological Characteristics of Varroa destructor (Parasitiformes, Varroidae) and Its Environmental Capacity as a Key Factor for Development of Varroosis Panzootia - Akimov, I.A.; Korzh, O.P. (Вестник зоологии, 2012)
By means of formalized schematic models of relationship with hosts the varroa mite uniqueness as a parasite is shown. The life cycle of this species requires the change of a host species at different stages of their development and physiological states. Thus the mite parasitizes not only a separate bee but a whole hive. The fact that the whole hive but not a single bee dies during varroosis development supports this idea. The impetus for this type of parasitism is the relative constancy of the environment in the hive supported by bees even in winter. Exactly this fact causes high pathogenicity of the varroa for the honey bee and its control complexity. С помощью формализованных схематических моделей взаимоотношения клеща варроа с хозяевами показана его уникальность как паразита. Жизненный цикл данного вида предусматривает обязательную смену особей хозяина, находящихся на разных стадиях развития и в разном физиологическом состоянии. Благодаря этому клещ паразитирует не на отдельной особи пчёл, а на улье в целом. Подтверждает эту мысль и тот факт, что в результате развития варрооза гибнет не отдельная пчела, а улей в целом. Стимулом для такого типа паразитизма является относительное постоянство среды в улье, поддерживаемое пчёлами даже в зимний период. Именно этот факт обуславливает высокую патогенность варроа для медоносной пчёлы и сложность борьбы с ним.